2017
DOI: 10.3390/su9081478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Distance on Open Innovation: Differences among Institutions According to Patent Citation and Reference

Abstract: Abstract:The main topic of this paper is the effects of distance between technology and the market, on open innovation. For this, we set up two research questions, as follows: Is there any relation between the distance between technology and the market, and open innovation? If there is, what differences are there in the relation among Fortune 500 companies, non-Fortune 500 companies, laboratories, universities, and start-ups? First, this study measured the distance between technology and the market of a patent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Another study measured the breadth of open innovation through the ratio of jointly applied patents from the total patents of a firm, and the depth of open innovation by the average number of joint applicants of each patent of a firm [37]. Another study analyzed the effect of distance on open innovation and its difference among institutions, and used the ratio of patents with joint applicants and the average number of joint applicants of each patent to measure the depth and breadth of open innovation, respectively [38]. In many studies, the co-invention index has been used to examine inter-and intranational collaborations in inventive activities, and the co-assignee index was used to examine intended inter-and intranational collaborations of the commercialization of inventive activities [39].…”
Section: Research Scope and Methodsmentioning
confidence: 99%
“…Another study measured the breadth of open innovation through the ratio of jointly applied patents from the total patents of a firm, and the depth of open innovation by the average number of joint applicants of each patent of a firm [37]. Another study analyzed the effect of distance on open innovation and its difference among institutions, and used the ratio of patents with joint applicants and the average number of joint applicants of each patent to measure the depth and breadth of open innovation, respectively [38]. In many studies, the co-invention index has been used to examine inter-and intranational collaborations in inventive activities, and the co-assignee index was used to examine intended inter-and intranational collaborations of the commercialization of inventive activities [39].…”
Section: Research Scope and Methodsmentioning
confidence: 99%
“…Thus, there are relations between the distance between technology and the market, and open innovation. The same studies indicate that the distance between technology and the market was found to moderate the open innovation effect in Fortune 500 companies and laboratories [66]. The recent CPMTT's projects and activities have proven to be effective and efficient in facilitating and developing technology transfer, whether we talk about studies and analyzes on the correlation of university curricula with the requirements of the Socio-Economic environment (studying and applying new technologies, alignment to new standards, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adoption of the complexity lens allows to better evaluate the transformational patterns affecting the development of innovation in an open approach enhanced by nonlinear interactions between different actors. For example, Yun et al [17] show that collaboration affect the innovation performance of an organization with a nonlinear u-shaped relation.…”
Section: Open Innovation and Complexity Theorymentioning
confidence: 99%